Less invasive surfactant administration for meconium aspiration syndrome - DAVID B NELSON; Arun Prasath; Etze Chotzoglou; Asmahan Ahmad; Efren Diaz; Patti Burchfield; L. Steven Brown; Katherine Stumpf; Venkatakrishna Kakkilaya (BMJ Paediatrics Open)
Background The role of less invasive surfactant administration (LISA) using a thin catheter in the management of meconium aspiration syndrome (MAS) is unclear.Study design A retrospective study of infants with MAS admitted between January 2016 and December 2023. Relevant characteristics and outcomes were compared between a group of infants receiving surfactant in conjunction with mechanical ventilation (MV) via an endotracheal tube (ETT-surf) and receiving LISA. Infants intubated at birth were excluded.Results Of the 113 infants admitted on continuous positive airway pressure (CPAP), 61 did not receive surfactant, 26 belonged to the ETT-surf group and 26 to the LISA group. Compared with the ETT-surf, a higher proportion of infants in the LISA group were exposed to chorioamnionitis and received a lower median fraction of inspired oxygen at birth and before surfactant therapy. Notably, infants in the LISA group had a lower need for MV (100 vs 23%, p<0.001), inhaled nitric oxide (iNO) (46% vs 12%, p=0.01) and a shorter median duration of hospital stay (14 vs 24 days, p=0.04). A subgroup analysis of infants with hypoxic respiratory failure on admission showed lower need for MV and duration of hospital stay with the LISA group compared with the ETT-surf group.Conclusions LISA was associated with a lower need for MV, iNO and a shorter duration of hospital stay in a select group of infants with MAS. Further prospective studies are necessary to evaluate the role of LISA in MAS.